Mjanmar - Marn, Tatjana (Vodniki LGD, 2015)
For the past half century, military dictatorship has left Burma (Myanmar), dubbed the Land of a Thousand Pagodas, practically completely isolated from the outside world. In addition to Buddhism, the predominant religion, this is also one of the reasons why its people have remained simple, open-hearted, and hospitable. There are more than 135 different ethnic groups living in Burma. Because of the country's diverse natural resources, it already attracted the attention of the global superpowers in the past, manifested in sixty years of British colonialism. It continues to be of interest today, especially because of its extensive supplies of natural gas, oil, gems, precious and rare metals, and valuable teakwood.Exceptionally picturesque Burma is also characterized by great biodiversity. The country is renowned for its elephants, many of which have been tamed. Rare white (albino) elephants are the most admired.The recommended ten-day tour first takes you to Burma's largest city, Yangon, after which you continue your trip across the Irrawaddy Valley to the city of Bagan with its thousands of temples, and on to the country's cultural center of Mandalay. Just before that you can climb Mount Popa, a dormant volcano, the mysterious abode of spirits known as the nats. You continue your trip onto the Shan Plateau to enjoy the peaceful flow of life at Lake Inle. If you have enough time, it is also worth visiting one of the seaside resorts.